Evaluasi Pembelajaran Pendidikan Agama Islam dalam Perspektif Kurikulum Merdeka - Siti Ria Farhaeni; Abdul Fattah; Suhirman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping students who are faithful, pious, and have noble character. However, PAI learning evaluation practices still tend to be cognitively oriented through written tests and memorization of material, resulting in less than optimal measurement of affective and psychomotor aspects, as well as the internalization of Islamic values in students' lives. Furthermore, teachers' understanding of the evaluation concept in the Independent Curriculum, particularly holistic and authentic evaluation, remains suboptimal. This situation indicates a gap between the ideal goals of PAI learning and evaluation practices implemented in the field. Therefore, this study aims to analyze the concept and implementation of Islamic Religious Education learning evaluation from the perspective of the Independent Curriculum.. This research employs a qualitative approach with a library research design. The research data were obtained through the examination of books, scientific journals, articles, and various literature sources relevant to PAI learning evaluation and the Merdeka Curriculum. Data analysis was conducted using content analysis through the stages of data condensation, data presentation, and descriptive-analytical conclusion drawing. The research results show that the concept of Islamic Religious Education (PAI) learning evaluation within the Independent Curriculum perspective is implemented through diagnostic, formative, and summative assessments based on the principles of student-centeredness, sustainability, flexibility, holistic, and authenticity. Its implementation serves not only as an instrument for measuring learning outcomes but also as a means of internalizing Islamic values, developing Islamic character, and strengthening students' spirituality through the comprehensive integration of cognitive, affective, and psychomotor aspects. Thus, the evaluation of Islamic Religious Education (PAI) learning within the Independent Curriculum has a more comprehensive, humanistic, and contextual orientation in supporting the achievement of Islamic education goals.